Potential dynamic regional brain biomarkers for early discrimination of autism and language development delay in toddlers - Wu, Shengjuan; Wen, Zhi; Yang, Wenzhong; Jiang, Chengcheng; Zhou, Yurong; Zhao, Zhiwei; Zhou, Aiqin; Liu, Xinglian; Wang, Xiaoyan; Wang, Yue; Wang, Hong; Lin, Fuchun (Frontiers in Neuroscience, 2023)
Background: The early diagnosis of autism in children is particularly important. However, there is no obvious objective index for the diagnosis of autism spectrum disorder (ASD), especially in toddlers aged 1–3 years with language development delay (LDD). The early differential diagnosis of ASD is challenging. Objective: To examine potential differences in the dynamic characteristics of regional neural activity in toddlers with ASD and LDD, to detect whether the differences were associated with ASD behaviors, and to provide an imaging biomarker for the early differential diagnosis of ASD and LDD. Methods: Dynamic regional homogeneity (dReHo) and dynamic amplitude of low-frequency fluctuations (dALFF) in 55 children with ASD and 31 with LDD, aged 1–3 years, were compared. Correlation analyses were also performed between dReHo and dALFF in areas with group differences and ASD symptoms. We further assessed the accuracy of dynamic regional neural activity alterations to distinguish ASD from LDD using receiver operating characteristic (ROC) analysis. Results: Compared with the LDD group, the ASD group showed increased dReHo in the left cerebellum_8/Crust2 and right cerebellum_Crust2, and decreased dReHo in the right middle frontal gyrus (MFG) and the right postcentral gyrus. Patients with ASD also exhibited decreased dALFF values in the right middle temporal gyrus (MTG) and right precuneus. Moreover, the correlation analysis showed that the Childhood Autism Rating Scale (CARS) score was negatively correlated with the dReHo of the left cerebellum_8/crust2 and right cerebellum_crust2. The dReHo value of the right MFG was negatively correlated with social self-help of the Autism Behavior Checklist (ABC) score. Conclusion: The pattern of resting-state regional neural activity variability was different between toddlers with ASD and those with LDD. Dynamic regional indices might be novel neuroimaging biomarkers that allow differentiation of ASD from LDD in toddlers.